U.C. Berkeley Alumni "Heavy" Gathering - Watkins, Howard::::::::: (1988)
Floor: Howard Watkins, Denise Morse, Dale Mesple, Terri Mesple, and Joe Barkett; Seated: Christine Watkins, David Atkinson, Kathy Muniz, David Morse, Janie Gumpert, Frank Gumpert, Jerry Neary, Bonnie Neary, Joe Barkett, Cynthia Nicholson, and Greg Nicholson